The Potential of Action Research in Boosting EFL Learners’ Experiential Learning and Metacognition - Lounis , Maha (Milev Journal of Research and Studies, 2022)
In the field of educational research, many studies are conducted by researchers in order to develop approaches and methods that inform educational practices and which can be adopted by teachers, learners or both. Action research is a type of educational research methods in which both the researcher and the participants are involved and share decision making during the different steps of the research.The action research process includesplanning, action, observation, evaluation and reflection, and feedback. The present paper is a theoretical research that sheds light on the overlap that exists between action research and experiential learning,on the one hand, andmetacognitive strategy instruction, on the other hand.Therefore, instead of focusing on the importance of action research for the researcher solely,emphasis is furtherput on the potential of action research in developing lifelong learning for EFL learners. The paper clarifies how action research engages EFL learners in experiential learning and how it boosts their metacognitive strategy use at the same time..